The influence of corporate financialization on asymmetric cost behavior: weakening or worsening - Zhu, Guanping; Hu, Wenxiu; Peng, Tao; Xue, Chaokai (Journal of Business Economics and Management, 2021)
This paper investigates the relationship between corporate financialization and asymmetric cost behavior using the Chinese listed companies over the period of 2009–2017. To examine the heterogeneous impacts of corporate financialization on asymmetric cost behavior, the paper analyzes the subsamples classified by different internal controls, compensation incentives, and agency problems. The multiple linear regression is used to test the research hypothesis. The research finds a negative relationship between corporate financialization and asymmetric cost behavior, which indicates that corporate financialization significantly weakens asymmetric cost behavior. Further studies show that the negative effect of corporate financialization on asymmetric cost behavior is mainly manifested in firms with good internal control quality, strong compensation incentive and low agency problem. On the contrary, the negative effect is insignificant in firms with poor internal control quality, weak compensation incentive and high agency problem. The results can not only enrich the existing literature, but also provide new evidence and inspiration for how to control asymmetric cost behavior of enterprises.First published online 29 October 2020